Self-Awareness and Its Relationship to Achievement Motivation among Students at College of Education for Girls - Adel Salem Al-Luaibi , Assist. Lect . Duha; Mohammed Khalifa , Assist. Lect. Duaa (Basra studies journal, 2026)
The paper "Self-Awareness and Its Relationship to Achievement Motivation among Students at the College of Education for Girls/ evening studies" aims at the following : 1- Identifying self-awareness among students at the College of Education for Girls/ evening studies.. 2- Identifying the achievement motivation among students at the College of Education for Girls/ evening studies. 3- Identifying the relationship between the level of self-awareness and its relationship to achievement motivation among married and unmarried female students at the College of Education for Girls/ evening studies. The sample of the current research was (100) female students at the College of Education for Girls / evening study. The researchers used the descriptive method. SPSS program for statistical analysis was used by the researchers too for analyzing the results. The results of the current research showed that there was a relationship between self-awareness and achievement motivation among students at the College of Education for Girls/ Evening studies. The sample of the current research has a high level of self-awareness and a high level of achievement motivation.